2012
DOI: 10.1371/journal.ppat.1002539
|View full text |Cite
|
Sign up to set email alerts
|

Novel Transmembrane Receptor Involved in Phagosome Transport of Lysozymes and β-Hexosaminidase in the Enteric Protozoan Entamoeba histolytica

Abstract: Lysozymes and hexosaminidases are ubiquitous hydrolases in bacteria and eukaryotes. In phagocytic lower eukaryotes and professional phagocytes from higher eukaryotes, they are involved in the degradation of ingested bacteria in phagosomes. In Entamoeba histolytica , which is the intestinal protozoan parasite that causes amoebiasis, phagocytosis plays a pivotal role in the nutrient acquisition and the evasion from the host defense systems. While the content of phagosomes and biochemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 60 publications
3
40
0
Order By: Relevance
“…We further demonstrated that CPBF1 is essential for the processing and lysosomal transport of EhCP-A5. On the other hand, CPBF8 binds to ␤-hexosaminidase ␣-subunit and lysozymes and transports them to phagosomes (19). We further showed that repression of CPBF8 by gene silencing decreased degradation of the Gram-positive bacillus Clostridium perfringens and in vitro cytopathic activity against mammalian cells.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…We further demonstrated that CPBF1 is essential for the processing and lysosomal transport of EhCP-A5. On the other hand, CPBF8 binds to ␤-hexosaminidase ␣-subunit and lysozymes and transports them to phagosomes (19). We further showed that repression of CPBF8 by gene silencing decreased degradation of the Gram-positive bacillus Clostridium perfringens and in vitro cytopathic activity against mammalian cells.…”
mentioning
confidence: 70%
“…Images were further analyzed using LSM510 software. We defined CPBF6-positive vacuoles based on criteria described elsewhere (19).…”
Section: Microorganisms and Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell-growth assay was performed as described previously (36) except that the starting cell number was set at 3,000 trophozoites/mL, and growing cells were counted at 48, 72, and 96 h. Cytopathic Activity Assay. The level of destruction of CHO cell monolayers was assessed as described previously (37), with minor modifications. Briefly, confluent CHO cells prepared by overnight culture in 24-well plates at 37°C and in 5% CO 2 were washed with Opti-MEM (Life Technologies) containing 1 mg/mL ascorbic acid and 5 mg/mL cysteine.…”
Section: Methodsmentioning
confidence: 99%
“…The plates were incubated under anaerobic conditions at 37°C for 60 min. After the plates were placed on ice for 10 min to detach trophozoites from the CHO cell monolayer, the number of CHO cells remaining in each well was measured using WST-1 reagent (Roche Diagnostics) as described previously (37).…”
Section: Methodsmentioning
confidence: 99%